Advancing gender equality through the Athena SWAN Charter for Women in Science: an exploratory study of women’s and men’s perceptions - Ovseiko, Pavel V. (Health Res Policy Syst, 2017)
BACKGROUND: While in the United Kingdom, Ireland, and Australia, higher education and research institutions are widely engaged with the Athena SWAN Charter for Women in Science to advance gender equality, empirical research on this process and its impact is rare. This study combined two data sets (free- text comments from a survey and qualitative interviews) to explore the range of experiences and perceptions of participation in Athena SWAN in medical science departments of a research-intensive university in Oxford, United Kingdom. METHODS: The study is based on the secondary analysis of data from two projects: 59 respondents to an anonymous online survey (42 women, 17 men) provided relevant free-text comments and, separately, 37 women participated in face-to-face narrative interviews. Free-text survey comments and narrative interviews were analysed thematically using constant comparison. RESULTS: Both women and men said that participation in Athena SWAN had brought about important structural and cultural changes, including increased support for women’s careers, greater appreciation of caring responsibilities, and efforts to challenge discrimination and bias. Many said that these positive changes would not have happened without linkage of Athena SWAN to government research funding, while others thought there were unintended consequences. Concerns about the programme design and implementation included a perception that Athena SWAN has limited ability to address longstanding and entrenched power and pay imbalances, persisting lack of work-life balance in academic medicine, questions about the sustainability of positive changes, belief that achieving the award could become an end in itself, resentment about perceived positive discrimination, and perceptions that further structural and cultural changes were needed in the university and wider society. CONCLUSIONS: The findings from this study suggest that Athena SWAN has a positive impact in advancing gender equality, but there may be limits to how much it can improve gender equality without wider institutional and societal changes. To address the fundamental causes of gender inequality would require cultural change and welfare state policies incentivising men to increase their participation in unpaid work in the family, which is beyond the scope of higher education and research policy. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12961-017-0177-9) contains supplementary material, which is available to authorized users.